Supertwistor description of ambitwistor strings - Berkovits, Nathan [UNESP]; Guillen, Max [UNESP]; Mason, Lionel (Springer Nature, 2020)
A new ambitwistor string is constructed based on a ten-dimensional super-twistor model for the massless superparticle. Although covariant quantization is complicated by reducibility issues, a light-cone gauge analysis can be easily performed. We show that with this analysis, this supertwistor ambitwistor string is equivalent to the RNS ambitwistor string in light-cone gauge. In order to make the comparison, we develop the light-cone gauge analysis of the RNS ambitwistor string which has some novel features in terms of its expression of the scattering equations through interaction point operators.
Keywords: BRST Quantization; Conformal Field Theory; Supergravity Models; Superstrings and Heterotic Strings